Association of dietary niacin intake with all-cause and cardiovascular mortality of adult patients with chronic kidney disease in the United States: results from NHANES 1999–2018 - Zhang, Chao; Cheng, Qi; Yang, Xinjun; Zhao, Wei; Luo, Kaifa; Qin, Yunlong (Frontiers in Nutrition, 2024)
Objective: The relationship between dietary niacin intake (DNI) and mortality rates among patients afflicted with chronic kidney disease (CKD) is a subject of debate. Utilizing data derived from the National Health and Nutrition Examination Survey (NHANES), this study adopts a retrospective cohort design with an aim to investigate the association in the American adult patients with CKD. Methods: A cohort study was conducted in the National Health and Nutrition Examination Survey (NHANES) between 2009 and 2018 that enrolled 6,191 CKD patients aged 20 years and above. We collected data on mortality through 31 December 2018. DNI was measured using a 24-hour recall method. The relationship between DNI levels and mortality from all causes and cardiovascular causes was analyzed using weighted Cox proportional hazards models. The Kaplan-Meier (K-M) survival curve was plotted to illustrate these associations. Results: Following a median monitoring period of 85 months, it was observed that 2,419 individuals (33.08%) succumbed to all causes, whereas cardiovascular-related deaths were recorded for 746 participants (10.45%). When controlling for confounders, an inverse relationship was established between DNI and mortality rates. Specifically, a marginal increase of 1 mg/day in DNI corresponded to a reduced Hazard Ratios (HRs) of 0.993 (0.987, 0.999) (p = 0.027) for all-cause mortality and 0.980 (0.969,0.991) (p < 0.001) for cardiovascular mortality. A further stratified analysis by quartiles of DNI, with the lowest quartile serving as the reference, revealed that the highest quartile was associated with HRs of 0.820 (0.697, 0.966) for all-cause mortality and 0.663 (0.465, 0.944) for cardiovascular mortality, both displaying a significant trend (p < 0.001). However, a subdivision of CKD patients by age showed that the protective effects of higher DNI were only confined to individuals aged 60 years and above but not to those under 60 years of age. Conclusions: A negative correlation between DNI and mortality due to all causes and cardiovascular issues among CKD patients aged 60 and above was revealed based on the datasets; however, this association was not observed in younger individuals under 60. Consequently, enhancing DNI might serve as a beneficial therapeutic strategy specifically for the older CKD demographic.